Investigating the relationship between meta-Cognition and Political Extremism - Geiser, Paula Jule (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2026)
This study investigated whether politically more extreme versus more moderate participants show differences in perceptual decision-making, metacognitive awareness, and their underlying neural mechanisms. Previous research has linked extreme political beliefs to overconfidence, cognitive rigidity, and reduced sensitivity to disconfirmatory evidence. However, to date, most studies relied on behavioral measures alone, leaving the neural underlyings of these effects underexplored. Using electroencephalography (EEG), this study investigated evidence accumulation, feedback processing, adaptive decision making, error awareness and metacognition in politically more extreme versus more moderate participants. Fifty-seven participants were divided into two groups and performed a random dot motion discrimination task. They reported both perceptual decisions (right/left movement of dots) and their confidence, while alternating between feedback and no-feedback conditions. Results showed better task performance in Moderates, but Extremists showed consistently higher confidence levels despite their lower accuracy and slower initial decisions reaction times. Neural evidence accumulation dynamics were overall similar across groups despite the behavioral differences. The study suggests that extremism may be related to top-down evaluative mechanisms and how evidence is weighted or interpreted. Future research on the cognitive mechanisms underlying political beliefs, could focus on subjective evaluation and replication with a larger and more extreme sample.
APPROVED
Keywords: political extremism; EEG; CPP; metacognition; feedback; error processing; adaptive decision-making; neurophysiology